Ageing in Prison. : Challenges and Support Programs for Aging in Prisons – A Literature Review ("Temas Sociais" Journal, 2024)
This study analyses the dynamics of ageing in a prison context, addressing the challenges faced by elderly prisoners and the effectiveness of social programmes aimed at improving their quality of life. Based on a systematic review of the literature, conducted according to the PRISMA protocol and covering 12 studies published between 2019 and 2024, five central dimensions were identified: insufficient infrastructure to meet the needs of this population, the impact of premature ageing on the prison environment, the limited effectiveness of social programmes, the need for palliative care, and structural and ethical barriers in the treatment of people with dementia. Despite some good practices, significant gaps remain in adapting policies and infrastructures. The conclusion is that ageing in prison requires urgent and integrated reforms that promote dignified ageing, health and social reintegration of older prisoners while ensuring full respect for their fundamental human rights.
Keywords: Ageing in a prison context; Social Programs; Prison; Literature Review